2023
DOI: 10.1111/irv.13212
|View full text |Cite
|
Sign up to set email alerts
|

Interactions among acute respiratory viruses in Beijing, Chongqing, Guangzhou, and Shanghai, China, 2009–2019

Zachary J. Madewell,
Li‐Ping Wang,
Natalie E. Dean
et al.

Abstract: BackgroundA viral infection can modify the risk to subsequent viral infections via cross‐protective immunity, increased immunopathology, or disease‐driven behavioral change. There is limited understanding of virus–virus interactions due to lack of long‐term population‐level data.MethodsOur study leverages passive surveillance data of 10 human acute respiratory viruses from Beijing, Chongqing, Guangzhou, and Shanghai collected during 2009 to 2019: influenza A and B viruses; respiratory syncytial virus A and B; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 49 publications
1
3
0
Order By: Relevance
“…Distinct seasonality in the circulation of respiratory viruses was observed, consistent with findings documented in the literature on virus-virus interactions and their effect on disease dynamics ( 58 60 ). A related study using SEDSS found distinct seasonal patterns in Puerto Rico, with respiratory viruses peaking in fall and winter, while arboviruses (e.g., dengue) peaked in summer and early fall, emphasizing the importance of recognizing these seasonal trends for accurate diagnosis and public health interventions in pediatric patients with AFI ( 10 ).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Distinct seasonality in the circulation of respiratory viruses was observed, consistent with findings documented in the literature on virus-virus interactions and their effect on disease dynamics ( 58 60 ). A related study using SEDSS found distinct seasonal patterns in Puerto Rico, with respiratory viruses peaking in fall and winter, while arboviruses (e.g., dengue) peaked in summer and early fall, emphasizing the importance of recognizing these seasonal trends for accurate diagnosis and public health interventions in pediatric patients with AFI ( 10 ).…”
Section: Discussionsupporting
confidence: 89%
“…Viral interference, a phenomenon highlighted in previous research, plays a role in shaping the observed patterns ( 61 , 62 ). At the population level, viral interference might be induced when an outbreak caused by one virus hastens or delays an epidemic caused by another virus ( 58 , 60 ). These results indicate that the seasonality of IAV typically precedes that of IBV each year, consistent with documented interactions between influenza types and subtypes that might involve cross-immunity mechanisms ( 63 , 64 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The decrease may be attributed to the reduced presence of common co-infecting viruses due to NPIs. HRV was frequently identified as a co-infecting agent, showing a positive correlation with HPIVs ( 13 ). The high occurrence of HPIVs and HRV co-infections could be linked to their transmission modes via direct contact, which might have been facilitated by lower adherence to preventive measures during NPIs.…”
Section: Discussionmentioning
confidence: 99%